Studi Literatur: Analisis Penerapan Model Pembelajaran Realistic Mathematic terhadap Kemampuan Pemecahan Masalah Matematika - Fauziah, Sifa; Tiurlina, Tiurlina; Alfarisa, Fitri (Didaktika, 2022)
Seeing the evolution of the situation and pandemic conditions that have not been resolved to date, causes researchers difficulty taking data on the ground, so researchers choose the study of literature. The following research is qualitative research using literary studies also known as library studies as this method of study. This study aims to 1) investigate how the ability to solve mathematical problems, especially in elementary school, 2) to know the analysis of the application of the model of the realistic mathematic approach, or the approach of the realistic mathematics of Indonesia (PMRI) and the last 3) to acquire the learning model of realistic mathematics can improve the problem solving of students of elementary school. One aspect that needs to be mastered based on the purpose of mathematical learning one of its aspects is that students are able to problem-solve including the capacity to understand the problem and make the model, work models and interpret the solutions obtained in the learning of math. Based on the analysis of the findings of sixteen (16) articles with relevant titles, the application of a realistic mathematical model was applied in order to improve the ability to solve problems. Based on an analysis of ten (10) articles with relevant titles, the effectiveness of solving mathematics problems in elementary school students proved to be still low.